Nitrogen-doped carbon dots based on grapefruit endocarp as well as preparation method and application of nitrogen-doped carbon dots

By using nitrogen-doped carbon dots based on the inner peel of grapefruit, the problem of insufficient coordination stability of single-coordinate sites in zinc ion batteries is solved, and efficient nitrogen doping treatment is achieved, which significantly improves the cyclic stability and conductive properties of zinc ion batteries.

CN119650890AActive Publication Date: 2025-03-18CHONGQING UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411767956.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In existing zinc ion batteries, the coordination stability of the single-coordinate site is weak, resulting in the hydrogen evolution reaction seriously affecting the cycle stability. The traditional carbon dots have not been treated with nitrogen doping, and the surface functional group activity is weak, making it impossible to form a stable coordination with Zn2+.

Method used

The nitrogen-doped carbon dots based on the grapefruit inner peel are prepared through hydrothermal reaction and high-efficiency nitrogen doping treatment, and the carbon dots on the surface are prepared to enhance the coordination stability with Zn2+.

Benefits of technology

The cyclic stability of zinc ion batteries is significantly improved, the cycle life of zinc-zinc symmetrical batteries is extended to 1400h, and the conductive properties and chemical stability of carbon dots are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650890A_ABST
    Figure CN119650890A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped carbon dot based on grapefruit endocarp, which is characterized in that the grapefruit endocarp and 2-methylimidazole are used as raw materials, the nitrogen-doped carbon dot NPP-CPDs is obtained through hydrothermal reaction, filtration, dialysis and freeze drying, the size is 10-20nm, and the nitrogen-doped carbon dot NPP-CPDs has a fluorescence emission peak; the surfaces of the carbon dots are loaded with imidazolyl, carboxyl and hydroxyl, and nitrogen sites can be stably coordinated with Zn < 2 + >. The preparation method comprises the following steps: 1, pretreating the pomelo endocarp PP; 2, preparation of R-NPP-CPDs (N, N-dimethylformamide); and (3) purifying the R-NPP-CPDs. According to the NPP-CPDs zinc ion battery electrolyte additive, the concentration of NPP-CPDs is 100-800 mg L <-1 >, and stable Zn-N bonds are formed by the NPP-CPDs and Zn < 2 + > on the surface of a zinc negative electrode through coordination; and the cycle performance of the zinc-zinc symmetric battery is 1400 to 1600 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon dots and the technical field of zinc ion batteries, and in particular to nitrogen-doped carbon dots based on grapefruit endocarp, and a preparation method and application thereof. Background Art

[0002] Zinc-ion batteries (ZIBs) have excellent theoretical capacity (820 mAh g -1 ), a lower redox potential (-0.763V vs SHE), and high safety brought by the use of aqueous electrolytes. However, the hydrogen evolution reaction seriously affects its cycle stability. According to the existing literature 1 (Cui, Yunwei, et al. "Challenges, strategies, and perspectives of anode protection in aqueous zinc-ion batteries." ACS Materials Letters 6.2 (2024): 611-626.), it can be seen that the current methods for improving the performance of aqueous zinc batteries mainly include optimizing the zinc electrode structure, constructing a functional protective layer, and adding electrolyte additives. Among them, although improving the electrode structure and constructing a protective layer can effectively alleviate the corrosion problem, such methods have the problems of high production cost and complex preparation process. The technical solution of adding corrosion inhibitors just has the advantages of low cost and easy operation.

[0003] At present, the principle of improving the performance of zinc-ion batteries by electrolyte additives is that the additives and Zn 2+ By coordination, H2O in the solvation structure is replaced, i.e., coordination effect. For example, existing document 2 (Lin, Yunhui, et al. "Highly reversible aqueous zinc-ion battery using the chelating agent triethanolamine as an electrolyte additive." CrystEngComm 24.45(2022):7950-7961.) uses triethanolamine TEA as an electrolyte additive, taking advantage of the fact that TEA can preferentially bind to Zn 2+ The coordination characteristics replace the H2O in the solvation structure and effectively prevent H2O and Zn 2+ Direct contact with the zinc electrode surface significantly inhibits the hydrogen evolution reaction. However, since TEA contains only one -NH2 coordination site, the 2+ The coordination stability is weak, resulting in a high coordination dissociation rate, which makes H2O re-combined with Zn 2+ Coordination.

[0004] A direct approach to solving the above problems is to provide additive molecules with multiple coordination sites to enhance the binding of Zn 2+ coordination stability. Among them, fluorescent carbon dots, as particles with multiple coordination sites, can be used as additives for zinc ion batteries. For example, existing document 3 (Yang, Shuhua, et al. "Hydrophilic and nanocrystalline carbonquantum dots enable highly reversible zinc-ion batteries." Green Chemistry 26.12 (2024): 7293-7301.) uses chitosan powder and acetic acid solution as raw materials, obtains CQDs by hydrothermal reaction, and applies the CQDs as electrolyte additives in zinc-zinc symmetric batteries, achieving a cycle life from the original 106h to 1000h. The problem with this technical solution is that since the obtained CQDs have not been doped, the surface functional group activity of the CQDs is weak and cannot react with Zn 2+ Form a stable coordination.

[0005] In order to further increase the interaction between the carbon dots and the zinc negative electrode surface, nitrogen-doped carbon dots can be used to introduce nitrogen coordination sites with stronger interaction. Since biomass materials have the characteristic of naturally containing nitrogen, the problem of lack of strong coordination sites in the above-mentioned traditional preparation methods can be solved. For example, existing document 4 (a preparation method and application of a grapefruit pulp peel-based porous carbon material: CN108584947A[P]. 2018-09-28.) uses the biomass material grapefruit pulp peel as a raw material, and obtains nitrogen-containing grapefruit pulp peel-based carbon material through low-temperature carbonization and activation treatment of porous carbon materials. When the carbon material obtained by this technical solution is applied to supercapacitor electrode materials, it reaches 117-315F / g at a current density of 0.5A / g, and obtains better energy storage performance. However, since the technical field of this technical solution is supercapacitors, the principle of supercapacitors determines that the required carbon materials only need to be doped with nitrogen with a low nitrogen content. Excessive nitrogen doping will lead to a decrease in performance. This is substantially different from the requirements for carbon materials in the field of zinc batteries. That is, the preparation method of grapefruit peel-based carbon materials in the existing document 4 is not applicable to the field of zinc batteries. The specific reason is that the carbon material of this technical solution has a small number of nitrogen coordination sites and has a problem of weak activity of nitrogen coordination sites.

[0006] Therefore, according to the existing literature, the current technology has the following technical problems:

[0007] 1. The coordination stability of the single coordination site is weak, and the coordination dissociation rate is high, which will cause H2O to re-combine with Zn 2+Therefore, multiple coordination sites need to be provided to enhance the coordination with Zn 2+ The coordination stability of

[0008] 2. Carbon dots that have not been doped with nitrogen have weak surface functional group activity, which results in poor adhesion to Zn 2+ Weak coordination stability;

[0009] 3. When carbon materials are applied to zinc-ion batteries, the nitrogen content and nitrogen source activity in conventional biomass materials cannot meet the application requirements of nitrogen doping. Summary of the invention

[0010] The purpose of the present invention is to provide a nitrogen-doped carbon dot based on grapefruit endocarp and a preparation method and application thereof. In view of the technical problems existing in the prior art, the present invention adopts the following principles and methods to solve the above problems:

[0011] 1. Select carbon dots with multiple coordination sites on the surface as additive molecules to solve the problem of weak coordination stability and high coordination dissociation rate of single coordination sites;

[0012] 2. By introducing additional highly active nitrogen sources, efficient nitrogen doping can be achieved to solve the problem of insufficient nitrogen content in traditional biomass materials, resulting in a small number of carbon dot coordination sites and weak activity.

[0013] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0014] A nitrogen-doped carbon dot based on grapefruit endocarp, characterized in that: grapefruit endocarp and 2-methylimidazole are used as raw materials, and after hydrothermal reaction, the nitrogen-doped carbon dot NPP-CPDs are obtained by filtering, dialysis and freeze drying;

[0015] The size of the NPP-CPDs is 10-20 nm, and under the condition of an excitation wavelength of 380 nm, it has a fluorescence emission peak at 455 nm; the surface of the NPP-CPDs is loaded with imidazole-Im, carboxyl-COOH and hydroxyl-OH, wherein the nitrogen site can react with Zn 2+ Stable coordination.

[0016] A method for preparing nitrogen-doped carbon dots based on grapefruit endocarp, comprising the following steps:

[0017] Step 1, pretreatment of the grapefruit endocarp, first, using the grapefruit endocarp, i.e. the spongy white endocarp as a raw material, drying it under certain conditions, and then, under certain conditions, ball milling the dried white grapefruit endocarp to obtain grapefruit endocarp powder, referred to as PP;

[0018] In step 1, the drying conditions are as follows: the drying temperature is 85° C. and the drying time is 8-12 hours;

[0019] In the step 1, the ball milling conditions are: the ball milling speed is 300-500 rpm, and the ball milling time is 4-6 h;

[0020] Step 2, preparation of R-NPP-CPDs, first, dissolving 2-methylimidazole in ultrapure water to obtain an imidazole solution, then placing the PP obtained in step 1 in the imidazole solution, and performing a hydrothermal reaction under certain conditions to obtain unpurified Raw-NPP-CPDs, referred to as R-NPP-CPDs;

[0021] In the step 2, the mass ratio of PP to 2-methylimidazole is 1:(1-1.5);

[0022] In step 2, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 160-200° C., and the hydrothermal time is 8-12 h;

[0023] Step 3, purification of R-NPP-CPDs, first, at room temperature, filter the R-NPP-CPDs obtained in step 2 to obtain a filtrate, then dialyze the filtrate under certain conditions, after the dialysis is completed, the solution in the dialysis bag is the purified NPP-CPDs, finally, freeze-dry the purified NPP-CPDs to obtain nitrogen-doped carbon dots based on grapefruit endocarp, referred to as NPP-CPDs;

[0024] In step 3, the filtering condition is to filter with a microporous membrane with a pore size of 0.22 μm; the dialysis condition is to perform dialysis with a dialysis bag with a MW of 1000;

[0025] In step 3, the dialysis method is to replace ultrapure water every 8 hours, and the total dialysis time is 24 hours;

[0026] In step 3, the freeze-drying method is to first freeze at a freezing temperature of -20 to -25°C for 24 hours, and then freeze-dry at a freeze-drying temperature of -45°C for 24 to 72 hours.

[0027] A zinc ion battery electrolyte additive based on nitrogen-doped carbon dots from grapefruit endocarp, wherein the concentration of NPP-CPDs in the ZnSO4 electrolyte is 100-800 mg L -1 NPP-CPDs can coordinate with Zn on the surface of zinc anode. 2+ It forms a stable Zn-N bond; when used as an additive in zinc-ion battery electrolyte, the cycle performance of the zinc-zinc symmetric battery is 1400-1600h.

[0028] The technical effects of the present invention are as follows:

[0029] Through transmission electron microscopy TEM test and fluorescence spectrum test, it is proved that NPP-CPDs have the basic characteristics of carbon dots;

[0030] Fourier transform infrared spectroscopy FTIR test proved that the surface of NPP-CPDs was loaded with imidazole-Im, carboxyl-COOH and hydroxyl-OH.

[0031] X-ray photoelectron spectroscopy XPS test proves that NPP-CPDs can react with Zn 2+ Stable coordination occurs, forming a Zn-N bond;

[0032] In the application of zinc-zinc symmetric batteries, after using NPP-CPDs as electrolyte additives, the zinc-zinc symmetric battery can be stably cycled for up to 1400h;

[0033] In the application of supercapacitors, after using NPP-CPDs as electrolyte additives, it was found that NPP-CPDs were only suitable for zinc-ion batteries but not for supercapacitors, which proved the specificity of NPP-CPDs in the application.

[0034] Therefore, the present invention has the following advantages over the prior art:

[0035] 1. Since carbon dots with multiple coordination sites on the surface are selected as zinc ion battery additives,

[0036] 1.1. The surface of carbon dots contains multiple coordination sites. This multi-site coordination mode significantly improves the coordination with Zn 2+ The coordination stability of the single coordination site is improved, thus avoiding the coordination instability problem caused by the high dissociation rate of the single coordination site.

[0037] 1.2. The preparation process of carbon dots is simple, controllable, and the raw materials are widely available and low in cost;

[0038] 1.3. Carbon dots have good chemical stability, can maintain structural integrity in electrolyte solutions, and are not prone to side reactions;

[0039] 2. Since efficient nitrogen doping is achieved by introducing an additional highly active nitrogen source,

[0040] 2.1. Nitrogen-doped carbon dots have strong surface functional groups and are more active than Zn 2+ High coordination stability, able to form a stable Zn-N bond;

[0041] 2.2. Nitrogen doping can improve the conductivity of carbon dots, contribute to the electron transfer efficiency of zinc ion batteries, and improve the overall cycle life of batteries;

[0042] 2.3. The type and proportion of nitrogen doping can be precisely controlled through the preparation process to meet the performance requirements of different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 TEM image of NPP-CPDs prepared in Example 1;

[0044] Figure 2 The fluorescence emission spectrum of NPP-CPDs prepared in Example 1;

[0045] Figure 3 FTIR graph of NPP-CPDs prepared in Example 1;

[0046] Figure 4 The XPS graphs of the zinc sheets immersed in the two electrolytes of ZnSO and NPP-CPDs-ZnSO in Example 1.

[0047] Figure 5 The time-voltage curves of the zinc-zinc symmetric battery with four electrolytes, namely ZnSO, NPP-CPDs-ZnSO, NOP-CPDs-ZnSO, and PP-CPDs-ZnSO in Example 1.

[0048] Figure 6 CV curves of supercapacitors with two electrolytes, NaSO and NPP-CPDs-NaSO, in Example 1. DETAILED DESCRIPTION

[0049] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0050] Example 1

[0051] A method for preparing nitrogen-doped carbon dots based on grapefruit endocarp, comprising the following steps:

[0052] Step 1, pretreatment of grapefruit endocarp, first, using grapefruit endocarp, i.e., spongy white endocarp as raw material, drying at a drying temperature of 85° C. for a drying time of 12 h, then ball milling the dried white grapefruit endocarp at a ball milling speed of 400 rpm for a ball milling time of 5 h to obtain grapefruit endocarp powder, referred to as PP;

[0053] Step 2, preparation of R-NPP-CPDs, first, dissolving 0.6 g of 2-methylimidazole in 60 mL of ultrapure water to obtain an imidazole solution, then placing 0.6 g of the PP obtained in step 1 in the imidazole solution, and performing a hydrothermal reaction at a hydrothermal temperature of 180° C. and a hydrothermal time of 8 h to obtain unpurified Raw-NPP-CPDs, referred to as R-NPP-CPDs;

[0054] Step 3, purification of R-NPP-CPDs. First, at room temperature, the R-NPP-CPDs obtained in step 2 are filtered with a microporous membrane with a pore size of 0.22 μm to obtain a filtrate. Then, the filtrate is dialyzed with a dialysis bag of MW 1000, with ultrapure water replaced every 8 hours for a total dialysis time of 24 hours. After the dialysis is completed, the solution in the dialysis bag is the purified NPP-CPDs. Finally, the purified NPP-CPDs are freeze-dried to obtain nitrogen-doped carbon dots based on grapefruit endocarp, referred to as NPP-CPDs.

[0055] The freeze-drying method is to first freeze at a freezing temperature of -20°C for 24 hours, and then freeze-dry at a freeze-drying temperature of -45°C for 48 hours.

[0056] In order to prove that NPP-CPDs are carbon dots, TEM test and fluorescence emission spectroscopy test were performed.

[0057] The TEM test results of NPP-CPDs are shown in Figure 1 As shown, the microscopic morphology of NPP-CPDs is ellipsoidal with a size of 15 nm;

[0058] The fluorescence emission spectrum test results of NPP-CPDs are as follows Figure 2 As shown, under the condition of excitation wavelength of 380 nm, NPP-CPDs has a fluorescence emission peak at 455 nm;

[0059] The comprehensive TEM test and fluorescence emission spectrum test results show that NPP-CPDs are carbon dots.

[0060] In order to prove the active sites on the surface of NPP-CPDs, FTIR test was performed. The test results are shown in Figure 3 As shown, NPP-CPDs contain characteristic peaks of C=N, NH bond, cyclic structure and stretching vibration of -OH and C=O, among which C=N, NH bond and cyclic structure are derived from imidazole-Im. The test results show that the surface of NPP-CPDs is loaded with imidazole-Im, carboxyl-COOH and hydroxyl-OH.

[0061] In order to prove the role of NPP-CPDs as an additive for zinc ion battery electrolyte, XPS test was carried out. The specific test method is as follows: first, the concentration of NPP-CPDs is 2 mol L -1 The ZnSO4 electrolyte was used as the basic electrolyte, referred to as ZnSO. Then, the concentration of NPP-CPDs was 200 mg L -1, add NPP-CPDs to the basic electrolyte to obtain NPP-CPDs electrolyte, referred to as NPP-CPDs-ZnSO. Finally, soak the zinc sheet in NPP-CPDs-ZnSO for 3 days. After soaking, XPS test can be performed. At the same time, in order to prove the effect of NPP-CPDs on the zinc sheet, the zinc sheet was soaked in the basic electrolyte and XPS test was performed as a reference. The test results are as follows Figure 4 As shown,

[0062] The test results of ZnSO are that it does not contain any characteristic peaks;

[0063] The test results of NPP-CPDs-ZnSO show that in addition to the characteristic peaks of CN and C=N of NPP-CPDs, there are also characteristic peaks of Zn-N bonds;

[0064] The test results show that adding NPP-CPDs can 2+ Stable coordination to form Zn-N bond.

[0065] In order to prove the effect of NPP-CPDs as an electrolyte additive on the performance of zinc-ion batteries, the cycling performance test of zinc-zinc symmetric batteries was carried out. At the same time, the cycling performance test of zinc-zinc symmetric batteries using ZnSO as the electrolyte was used as a reference. The test results are shown in Figure 2. Figure 5 As shown, at a current density of 1 mA cm -2 、Capacity 0.5mAh cm -2 Under the condition of , ZnSO can stably circulate for 150h;

[0066] NPP-CPDs-ZnSO can be stably cycled for 1400 h;

[0067] The test results show that the addition of NPP-CPDs can significantly improve the cycle performance of zinc-zinc symmetric batteries, with an increase of 833.3%.

[0068] In order to prove the specificity of NPP-CPDs, that is, its suitability as an electrolyte additive for zinc ion batteries, CV tests were performed using NPP-CPDs as an electrolyte additive for supercapacitors. The specific method for preparing supercapacitors is as follows: first, a 2 mol L -1 The Na2SO4 electrolyte was used as the basic electrolyte, referred to as NaSO. Then, the concentration of NPP-CPDs was 200 mg L -1, NPP-CPDs was added to the basic electrolyte to obtain NPP-CPDs electrolyte, referred to as NPP-CPDs-NaSO. Finally, CMK-3 was used as the positive and negative electrode materials, and NPP-CPDs-NaSO was used as the electrolyte to assemble the supercapacitor for CV test. At the same time, NaSO was used as the electrolyte to assemble the supercapacitor for CV test as a reference. The test results are shown in Figure 6 As shown, at a scan rate of 10 mV / s, the potential ranges from -2.5 V to 2.5 V.

[0069] The curve of NaSO shows a typical quasi-rectangular shape;

[0070] The curve shape of NPP-CPDs-NaSO is similar to that of NaSO, showing a typical rectangular shape. However, the difference is that the current density of NPP-CPDs-NaSO has increased. The reason is that NPP-CPDs-NaSO in the supercapacitor not only has no corrosion inhibition effect, but also induces hydrogen or oxygen evolution side reactions, which reduces the performance of the supercapacitor.

[0071] The test results show that although under normal circumstances, batteries and supercapacitors have similar requirements for additives, NPP-CPDs are only suitable as zinc-ion battery electrolyte additives, but not as supercapacitor additives, which proves that NPP-CPDs are specific.

[0072] Similarly, compared with the existing document 4 described in the background, although this technical solution also uses grapefruit peel as the biomass raw material, since the technical field involved in this technical solution is supercapacitors, a calcination process is used to prepare porous carbon materials, thereby obtaining corresponding technical effect improvements; however, as can be seen from the background analysis, the technical solution of the existing document 4 is also not applicable to the zinc battery technology field of the present invention, which also proves that the NPP-CPDs of the present invention has specificity.

[0073] In order to demonstrate the effect of grapefruit endocarp on the performance of nitrogen-doped carbon dots, that is, the role of grapefruit endocarp in the technical solution, Comparative Example 1 is provided, a nitrogen-doped carbon dot based on orange peel.

[0074] Comparative Example 1

[0075] A method for preparing nitrogen-doped carbon dots based on orange peel, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, orange peel is used instead of grapefruit endocarp as a biomass carbon source, and the obtained carbon dots are referred to as NOP-CPDs.

[0076] The cycling performance test results of the zinc-zinc symmetric battery of NOP-CPDs are shown in Figure 5 As shown, at a current density of 1 mA cm -2、Capacity 0.5mAh cm -2 Under the condition of , NOP-CPDs-ZnSO can stably circulate for 180h;

[0077] Compared with ZnSO, the addition of NOP-CPDs can slightly improve the cycling performance of Zn-Zn symmetric batteries, with the improvement being only 20%;

[0078] Compared with the NPP-CPDs-ZnSO of Example 1, it can be seen that the nitrogen-doped carbon dots prepared based on grapefruit endocarp and orange peel have substantial and significant differences in the cycling performance of zinc-zinc symmetric batteries.

[0079] The reason is that according to reference 1 (Feng Kun. Research on the Composition and Activity of Peels of Main Pomelo Species in China [D], 2019), the cellulose content in pomelo peel reaches 30%-40%, and the structure of its fiber tissue determines that it can form a dense and stable carbon skeleton structure after carbonization, providing a better surface area and pore structure, which is conducive to loading active substances;

[0080] At the same time, according to reference 2 (Liu Xuefeng, Yang Mei, Xiang Pingwei, et al. Research Progress on Important Components of Citrus Peel and Their Applications [J], Food and Fermentation Industries, 2024, 50(2): 379-388), the cellulose content of orange peel is only 20%-30%, and the structure of its fiber tissue determines that the carbon skeleton structure formed after carbonization is a loose structure, resulting in the inability to maintain stability after loading active substances.

[0081] Therefore, according to the existing literature, although grapefruit and orange belong to the genus Citrus of the Rutaceae family, that is, they have a high degree of similarity as biomass raw materials, the differences in their components represented by cellulose content and their fiber tissue structure directly lead to substantial differences in the structure of the carbon dots obtained after carbonization.

[0082] In order to demonstrate the effect of 2-methylimidazole on the performance of nitrogen-doped carbon dots, that is, the role of 2-methylimidazole in the technical solution, comparative example 2 is provided, which is a grapefruit endocarp carbon dot without adding 2-methylimidazole.

[0083] Comparative Example 2

[0084] A method for preparing grapefruit endocarp carbon dots without adding 2-methylimidazole, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 2, 2-methylimidazole is not added, and the obtained carbon dots are referred to as PP-CPDs.

[0085] The cycling performance test results of the zinc-zinc symmetric battery of PP-CPDs are shown in Figure 5 As shown, at a current density of 1 mA cm -2、Capacity 0.5mAh cm -2 Under the condition of , PP-CPDs-ZnSO can stably cycle for 240h.

[0086] Compared with ZnSO, the addition of PP-CPDs can slightly improve the cycling performance of Zn-Zn symmetric batteries, with the improvement being only 60%;

[0087] Compared with the NPP-CPDs-ZnSO of Example 1, it can be seen that the cycle stability can be significantly improved by adding 2-methylimidazole for nitridation.

[0088] The reason is that 2-methylimidazole can be used as a nitrogen source to load 2-methylimidazole on the grapefruit endocarp for nitrogen doping, which can increase the active sites of the obtained PP-CPDs and thus make the PP-CPDs interact with the Zn on the surface of the Zn electrode. 2+ The Zn-N bond is formed, the adsorption effect of PP-CPDs carbon dots on the surface of the zinc electrode is improved, the contact between H2O and the zinc electrode is reduced, thereby inhibiting the occurrence of hydrogen evolution reaction and effectively improving the cycle stability of the zinc electrode.

Claims

1. A nitrogen-doped carbon dot based on grapefruit endocarp, characterized in that: Using grapefruit endocarp and 2-methylimidazole as raw materials, nitrogen-doped carbon dots NPP-CPDs were obtained after hydrothermal reaction, filtration, dialysis and freeze-drying.

2. The nitrogen-doped carbon dots according to claim 1, characterized in that: The size of the NPP-CPDs is 10-20 nm, and under the condition of an excitation wavelength of 380 nm, it has a fluorescence emission peak at 455 nm; the surface of the NPP-CPDs is loaded with imidazole-Im, carboxyl-COOH and hydroxyl-OH, wherein the nitrogen site can react with Zn 2+ Stable coordination.

3. A method for preparing nitrogen-doped carbon dots based on grapefruit endocarp, characterized in that The following steps are involved: Step 1, pretreatment of grapefruit endocarp, first, using grapefruit endocarp, i.e. spongy white endocarp as raw material, drying under certain conditions, then ball milling the dried white grapefruit endocarp under certain conditions to obtain grapefruit endocarp powder, referred to as PP; Step 2, preparation of R-NPP-CPDs, first, dissolving 2-methylimidazole in ultrapure water to obtain an imidazole solution, then placing the PP obtained in step 1 in the imidazole solution, and performing a hydrothermal reaction under certain conditions to obtain unpurified Raw-NPP-CPDs, referred to as R-NPP-CPDs; Step 3, purification of R-NPP-CPDs. First, at room temperature, filter the R-NPP-CPDs obtained in step 2 to obtain a filtrate. Then, dialyze the filtrate under certain conditions. After the dialysis is completed, the solution in the dialysis bag is the purified NPP-CPDs. Finally, freeze-dry the purified NPP-CPDs to obtain nitrogen-doped carbon dots based on grapefruit endocarp, referred to as NPP-CPDs.

4. The preparation method according to claim 3, characterized in that: In step 1, the drying conditions are as follows: the drying temperature is 85° C. and the drying time is 8-12 hours; In the step 1, the ball milling conditions are: the ball milling speed is 300-500 rpm, and the ball milling time is 4-6 hours.

5. The preparation method according to claim 3, characterized in that: In the step 2, the mass ratio of PP to 2-methylimidazole is 1:(1-1.5); In step 2, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 160-200° C., and the hydrothermal time is 8-12 h.

6. The preparation method according to claim 3, characterized in that: In step 3, the filtering condition is to filter with a microporous membrane with a pore size of 0.22 μm; the dialysis condition is to perform dialysis with a dialysis bag with a MW of 1000; In step 3, the dialysis method is to replace ultrapure water every 8 hours, and the total dialysis time is 24 hours; In step 3, the freeze-drying method is to first freeze at a freezing temperature of -20 to -25°C for 24 hours, and then freeze-dry at a freeze-drying temperature of -45°C for 24 to 72 hours.

7. A zinc ion battery electrolyte additive based on nitrogen-doped carbon dots from grapefruit endocarp, characterized in that: The concentration of NPP-CPDs in ZnSO4 electrolyte is 100-800 mg L -1 NPP-CPDs can coordinate with Zn on the surface of zinc anode. 2+ Forming a stable Zn-N bond.

8. The zinc ion battery electrolyte additive according to claim 7, characterized in that: When used as an additive for zinc-ion battery electrolyte, the cycle performance of zinc-zinc symmetric battery is 1400-1600h.

Citation Information

Patent Citations

  • Preparation method of nitrogen doped carbon based quantum dot

    CN105176528A

  • Nitrogen-doped carbon quantum dot material as well as preparation method and application thereof

    CN107446578A

  • Simple preparation method of carbon material with grapefruit flesh as raw material

    CN114477175A

  • Zinc ion battery electrolyte containing carbon dots as well as preparation method and application of zinc ion battery electrolyte

    CN115911592A

  • Fluorescence display fibrous aqueous zinc ion battery and preparation method and application thereof

    CN116525974A